Consideration the Effects of Water Sector Investment on Economic Growth in Iran - Tir, Norouz Aghajani; Momeni, Farshad; Boboevich, Ganiev Tavarali (International Journal of Sustainable Development & World Policy, 2014)
This paper studies the causality relationship between water sector investment and economic growth and other sector such as agriculture, industry and mine, services, and petroleum sectors in Iran, using panel data approach, from annual data covering the period of 1980 to 2010. The short-run cointegration estimation support the relationship between our variables. In this paper we show the effects of water sector investment on production function of Solow growth model for this purpose we use econometric method based on Panel Data.The results show low efficiency in water industry. Solow Growth Model for different sectors (agriculture, industry and mine, services, and petroleum sectors) in Iranian economy implies that the elasticity of water investment in agricultural sector is significant, and positive, with the amount of 1.3%. Also results show that the investment effect of water sector for groundwater discharge is about 2.4 percent which is significant. Finally the results show that conversely relationship for surface waters with the amount of about -2.7%.